Predictors of Outcomes for Older Adults Participating in Calmer Life, a Culturally Tailored Intervention for Anxiety. Issue 3 (27th May 2017) - Conti, Elizabeth C.; Barrera, Terri L.; Amspoker, Amber B.; Wilson, Nancy; Shrestha, Srijana; Wagener, Paula; Armento, Maria; Evans-Hudnall, Gina; Cummings, Jeremy P.; Kunik, Mark E.; Stanley, Melinda A.
ABSTRACT: Objective : Determine predictors of reduced worry and anxiety for older adults participating in the pilot phase of Calmer Life, a modular, personalized cognitive-behavioral treatment for worry. Methods : Underserved adults (N = 54) over age 50 participated. Therapists were either experts (Ph.D. or Master's) or nonexpert providers (case managers, community health workers, and bachelor's level). Participants completed the Penn State Worry Questionnaire—Abbreviated (PSWQ-A) and the Geriatric Anxiety Inventory—Short Form (GAI-SF) before treatment and at 3 months. Results : Demographic and clinical variables were individually entered into separate regression equations, controlling for pretreatment scores, to determine their associations with post-treatment 1) PSWQ-A and 2) GAI-SF scores. Only younger age and African American race were significant (p < .05) univariate predictors of higher post-treatment PSWQ-A scores. African American race was also a significant predictor of higher post-treatment GAI-SF scores. Conclusions : African American participants had higher post-treatment PSWQ-A and GAI-SF scores than White and Hispanic participants. Younger age was also associated with more severe PSWQ-A post-treatment scores. Clinical Implications : Younger participants may experience additional stressors (e.g., caregiving, working) compared with older participants. Smaller decreases in anxiety in African Americans point to the need for continued focus and additional modification of interventions.